Microring resonator-based logic module for all optical information processing. Issue 15 (2nd September 2018) - Katti, Rohan; Prince, Shanthi
Abstract: We propose an all-optical logic module based on switching in microring resonators due to free carrier induced two-photon absorption. The proposed logic module is implemented using two microring resonators, and with the addition of beam combiner(s), it can be configured to perform different arithmetic and logical operations based on different combinations of input bits. The design is analysed mathematically in terms of coupling between the ring resonator and waveguides. The logic module can also be configured as a half adder and a half subtractor, suitable for all-optical information processing applications. Simulation results are in good agreement with the theoretical calculations and are presented in this paper.